دور الإعلام الاجتماعي في تنمية المعرفة السياسية لدى الشباب الجامعي -دراسة ميدانية على عينة من الطلبة المستخدمين بجامعة قالمة - حمدي, بثينة (University of Eloued جامعة الوادي, 2017)
الملخص سعت هذه الدراسة إلى الإجابة على مجموعة من الأسئلة الملحة حول دور وسائل الإعلام الجديدة ممثلة في مواقع الإعلام الاجتماعي في إمداد الشباب الجامعي بالمعلومات السياسية ومن ثم مساهمتها في إكسابهم المعرفة السياسية ، و ذلك بإجراء دراسة ميدانية على عينة قواها 120 مفردة من الشباب الجامعي بكلية العلوم الإنسانية و الاجتماعية بجامعة قالمة . و قد توصلت الدراسة إلى المكانة البارزة التي احتلها الإعلام الاجتماعي لدى المبحوثين في مجال استقاء المعلومات السياسية ، من خلال استخدام المبحوثين لمختلف الصفحات الإعلامية الموجودة على هذه المواقع و كذا تفاعلهم معها عن طريق التعليقات و المشاركات ، كما برزت معرفة الطلبة بأغلب القضايا و المواضيع السياسية المطروحة محليا و إقليميا و دوليا ، و أكدوا على زيادة وعيهم بمختلف الأحداث السياسية و تصاعد اهتمامهم بها بفضل استخدامهم لمواقع الميديا الاجتماعية This study aimed at answering some important questions regarding the role of the recent mass media, like social networks, in providing the university youth with the political information, which will lead to increase their political knowledge. A sample of 120 of the university youth in the college of Humanities and Social Studies in Guelma University has been taken a a case study. This study concluded to the important role of the social media in the respondent’s life in the field of political information, through the respondents' access to different pages on these Web Sites and interacting through commenting and sharing. In addition, the social media enhanced the students’ knowledge of most of the political issues and topics locally, regionally and internationally. Mean while, the university youth assured that their awareness and interest of the different political events has been increased thanks to the social medi
The Role of Social Media in developing the political knowledge of the university youth: A Case study of students in the University of Guelm
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: الإعلام الاجتماعي ، الشباب الجامعي ، المعرفة السياسية; : social media, university youth , political awareness